2020
DOI: 10.1039/d0sc00361a
|View full text |Cite
|
Sign up to set email alerts
|

New reductive rearrangement of N-arylindoles triggered by the Grubbs–Stoltz reagent Et3SiH/KOtBu

Abstract: N-Arylindoles are transformed into dihydroacridines in a new type of rearrangement, through heating with triethylsilane and potassium tert-butoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This preference for N‐linked substrates is borne out by very recent reductive rearrangements of N‐aryl indoles in the presence of the same reagents, i. e . Et 3 SiH and KO t Bu …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This preference for N‐linked substrates is borne out by very recent reductive rearrangements of N‐aryl indoles in the presence of the same reagents, i. e . Et 3 SiH and KO t Bu …”
Section: Resultsmentioning
confidence: 99%
“…In 2013, Grubbs et al . reported that heating Et 3 SiH with KO t Bu afforded a novel reagent which has since been shown to carry out a wide range of chemical transformations . (Schemes and ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing the reaction at −30°C allowed ( E )‐ 4 to isomerize into ( Z )‐ 4 before work‐up. According to the recent report by Tuttle and Murphy, [ 27 ] the radical anion of 3 can fragment before the second electron injection to afford the corresponding distal radical anion, that is, styryl radical/lithium diarylamide connected species. Although I cannot rule out the possibility of Tuttle/Murphy's process operating, I am inclined to prefer the fragmentation from dianion 6 , on the basis of the facile ring‐opening even at −78°C, the exclusive formation of ( E )‐ 4 as the kinetic product, and the necessity of an excess amount of lithium powder, together with the literature.…”
Section: Aromatic Metamorphosis Of Indoles Through Electron Injectionmentioning
confidence: 99%
“…A novel reducing system, consisting of the reagent-pair, triethylsilane and potassium tert-butoxide was reported by Stoltz, Grubbs et al in 2013. 1 The combination of the two reagents has since been investigated by a number of research groups [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and provides a range of distinctive reaction types, arising through an unprecedented menu of reactive intermediates formed in the reaction, including triethylsilyl radicals 1, silanates 2 as hydrogen atom donors to both closed shell molecules and to radicals, and as potential hydride ion donors, and tert-butoxytriethylsilyl radical anions 3 as a very powerful electron donor. Exposing substrates simultaneously to multiple reactive intermediates is not routinely encountered in organic chemistry, other than in modelling of prebiotic conditions, 16 and so the variety of reactive intermediates produced by this reagent pair provides opportunities to witness unusual outcomes.…”
Section: Introductionmentioning
confidence: 99%